EVALUATING THE NEXUS BETWEEN FINANCIAL DEEPENING AND STOCK MARKET IN NIGERIA - Nnenna, Okoli Margaret (European Scientific Journal, ESJ, 2012)
The paper examines the relationship between financial deepening and stock market returns and volatility in the Nigerian stock market. Estimation depending on the measures of financial deepening and market returns were evaluated using GARCH (1, 1) model. Four modeled equations were estimated and analysed. Financial deepening is represented by two variables, the ratio of the value of stock traded to GDP (FD1t) and the ratio of market capitalization to GDP (FD2t). Empirical results revealed that financial deepening (FD1t) measured as the ratio of value of stock traded to GDP do not affect the stock market and there is no news about volatility. But financial deepening (FD2t) measured as the ratio of market capitalization to GDP affect the stock market. It indicated that financial deepening reduces the level of risk (volatility) in the stock market. Result also recorded that the conditional volatility of returns is slightly persistent. Policy implications emanating from the study is that efforts should be made to improve financial development in the country by increasing the range of financial assets. Deepening finance intermediation may promote economic growth by mobilizing more investments, and lifting returns to financial resources, which raises productivity. Increased investors. confidence and less risk perception by them, will invariably further boost the market and ginger growth.